Quota Brokers. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This paper examines the role of middlemen (brokers) in an imperfect secondary market for quota licenses. Middlemen facilitate trade when markets are thin, as potential buyers and sellers find it difficult to meet and transact directly. However, in thin markets, middlemen also have the ability to influence the terms on which trades occur, and the wedge they create between the buying and selling price limits the extent to which they facilitate trade. We develop and simulate a model of quota broker behavior to examine their welfare implications.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Licensing; Market Power; Market Structure and Pricing; Rationing; WP